PENINGKATAN PROFESIONALISME MGMP PAI MELALUI PELATIHAN PENGEMBANGAN BAHAN AJAR BERBASIS TEKNOLOGI METAVERSE - ahmad shofiyuddin (Dharma: Jurnal Pengabdian Masyarakat, 2026)
This community service aims to enhance the professionalism of PAI MTs Teachers’ Working Group (MGMP) in Bojonegoro Regency through training on learning material development using Augmented Reality (AR) and Virtual Reality (VR) technologies, supporting the achievement of Asta Cita 4, particularly in strengthening human resource quality and digital transformation in education. The program applied the Asset-Based Community Development (ABCD) approach, emphasizing the empowerment of local assets. In the discovery phase, participants’ existing competencies, collaborative culture, and available digital infrastructure were identified. The dream phase formulated a shared vision for developing immersive and interactive PAI learning materials using AR and VR. The design phase focused on creating training modules, learning scenarios, and AR/VR-based instructional prototypes using the TPACK framework. The destiny phase included implementation, mentoring, pilot testing, and continuous reflection. Quantitative evaluation showed that participants’ technological literacy improved by 48%, their ability to design AR-based learning content increased by 42%, and the effectiveness of VR-based simulation in the classroom was rated at 4.6 out of 5 in participant satisfaction surveys. The program produced AR and VR learning material prototypes and strengthened a digital practice community within MGMP, fostering sustainable professional development. These results indicate that the ABCD approach effectively enhances teacher professionalism by leveraging community assets while accelerating the adoption of immersive technologies in madrasah education.